Chinese medicine and environmental disease - Lei Wang; Kun Qiao; Hengtai Zhang; Kezhong Zhang (Wolters Kluwer Medknow Publications, 2016)
Environmental diseases represent the major challenge to the modern human health. Despite the increased public health challenges, "Western Medicine," or modern medicine, has limited solutions in regard to the prevention or treatment of environment-associated complex chronic diseases. In contrast, "Integrative or Alternative Medicine," particularly Traditional Chinese Medicine (TCM), shows promising health benefits in improving the symptoms or even curing some of chronic environmental diseases. TCM defines disease as a disharmony or imbalance in the functions of inner body energy circuit or interactions between the human body and the environment. The principals of diagnosis and treatment of TCM are to identify the patterns of disharmony and restore systemic harmony inside human body and between the human body and environment. These principles are well in line with the etiology and development of modern environmental diseases. In this review, we summarize some progress in using TCM to treat environment-associated, modern human common diseases.